A intervenção da dança em mulheres pós-tratamento de câncer de mama e sua relação com a qualidade de vida - Ferreira, Fátima Ribeiro (2012)
Introduction: Breast cancer incidence is associated with age of those affected patients. The quality of life (QOL) of patients with breast cancer is an important aspect to be considered in the healthy aging process. It is important to consider new options for intervention on the QOL of women after treatment of breast cancer. One alternative is to use dance as a therapeutic resource. The aim of this study was to evaluate the association between dance intervention and QOL in women with breast cancer, as well as pain perception. Methods: A sample of 15 women, 50 to 79 yearsold, outpatients from Oncogenetics, Mastology and Oncology, Hospital de Clinicas de Porto Alegre (HCPA) participated in a ballroom dancing intervention of 13 sessions, 1:30 weekly. Validated instruments were used to assess the quality of life (WHOQOL-Bref and Fact B),and the pain visual analog scale. All participants signed Informed Consent Forms. After the intervention of dance, focus groups was used in order to evaluate the experience of study participants.Results: The quantitative results showed no statistically significant differences when comparing the periods before and after dance intervention. However, qualitative data showed relevant changes reported by the participants in terms of pain, social integration and selfesteem. Conclusion: The reports presented by the patients showed the importance attached to dance, which allowed to combine physical activity with social interaction.